The ARF tumor suppressor targets PPM1G/PP2Cγ to counteract NF-κB transcription tuning cell survival and the inflammatory response - Hyder, Usman (2020)
Inducible transcriptional programs mediate the regulation of key biological processes and organismal functions. Despite their complexity, cells have evolved mechanisms to precisely control gene programs in response to environmental cues to regulate cell fate and maintain normal homeostasis. Upon stimulation with proinflammatory cytokines such as tumor necrosis factor-α (TNF), the master transcriptional regulator nuclear factor (NF)-κB utilizes the PPM1G/PP2Cγ phosphatase as a coactivator to normally induce inflammatory and cell survival programs. However, how PPM1G activity is precisely regulated to control NF-κB transcription magnitude and kinetics remains unknown. Here, we describe a mechanism by which the ARF tumor suppressor binds PPM1G to negatively regulate its coactivator function in the NF-κB circuit thereby promoting insult resolution. ARF becomes stabilized upon binding to PPM1G and forms a ternary protein complex with PPM1G and NF-κB at target gene promoters in a stimulidependent manner to provide tunable control of the NF-κB transcriptional program. Consistently, loss of ARF in colon epithelial cells leads to up-regulation of NF-κB antiapoptotic genes upon TNF stimulation and renders cells partially resistant to TNFinduced apoptosis in the presence of agents blocking the antiapoptotic program. Notably, patient tumor data analysis validates these findings by revealing that loss of ARF strongly correlates with sustained expression of inflammatory and cell survival programs. Collectively, we propose that PPM1G emerges as a therapeutic target in a variety of cancers arising from ARF epigenetic silencing, to loss of ARF function, as well as tumors bearing oncogenic NF-κB activation.